## jazzyfa30 2 years ago Solve the equation by using the Square Root Property. x^2 = 21 - 4x

1. hartnn

do you know how to complete the square ?

2. jazzyfa30

no

3. hartnn

x^2+4x = 21 here, the co-efficient of 'x' is 4 so, divide it by 2, and take its square, what u get ?

4. jazzyfa30

4/2=2 square root is 1.4

5. hartnn

we need to SQUARE the result so, 2^2 = 4 now, we add this on both sides., x^2+4x+4 = 21+4 = 25 got this ?? notice something about left side ?

6. jazzyfa30

7. hartnn

yes, i added the result (here, we got 4) to both sides now notice that left side is a perfect square! isn't it ?

8. jazzyfa30

yes

9. hartnn

x^2+4x+4 is square of what ?

10. jazzyfa30

2

11. hartnn

4 is the square of 2 x^2+4x+4 will be square of \(\large (x+2) \\ (x+2)^2 =x^2+4x+4\) so we have \((x+2)^2=25\) take square root of both sides , what u get ?

12. jazzyfa30

x+1.4=5

13. jazzyfa30

x+2=5 my b

14. hartnn

yes.. just put +/- in front of 5 x+2=5 or x+2=-5

15. hartnn

can you solve those 2 easy equations ? x+2= 5....x =.. ? x+2=-5, ....x=....?

16. jazzyfa30

x=3 anx =-7

17. hartnn

correct! good work :)

18. JAYLINB

JAZZY ITS BRONX

19. jazzyfa30

hi what happenedy u not on ur regulrs account

20. jazzyfa30

Solve the equation by factoring: x2 = 18 - 3x

21. GoldPhenoix

Does x2 = x^2 And does the = sign suppose to be a + sign?

22. jazzyfa30

sorry im still waking up x^2=18-3x

23. GoldPhenoix

I don't think you can factor that.

24. jazzyfa30

sorry @hartnn i fell asleep i was up all night literally i didnt geta ounce of sleep until after w finished the problem we just finished

25. hartnn

\(x^2+3x-18=0\) can you tell me 2 numbers with sum = 3 and product = -18 ?

26. jazzyfa30

6 and -3

27. hartnn

get some rest then! you can continue in the morning ? yes! 6 and -3 are correct :)

28. jazzyfa30

it is morning hear its 8:30 am

29. hartnn

so, split up, 3x = 6x-3x \(x^2+6x-3x-18=0\) factor out x from 1st 2 terms and -3 from last 2.....can you ?

30. jazzyfa30

(x+6)-(x-3) i think

31. hartnn

there's no - *minus* sign \((x+6)(x-3)=0\) is correct final answer! good :)

32. jazzyfa30

oh yeah im sorry yall

33. hartnn

and since you need to solve find x from x+6=0 and x-3=0

34. jazzyfa30

-6 andd 3

35. hartnn

\(\large \checkmark \)

36. jazzyfa30

thank you 5 more and im going to sleep

37. hartnn